The use of simulation training to accelerate the rate of forward ice skating skill acquisition - Washington, N. J.; Dogramaci, S.; Steel, K. A.; Ellem, E. (International Journal of Kinesiology & Sports Science, 2016)
Background: Australia`s interest and participation in ice hockey is increasing, however a lack of access to facilities means familiarity with this sport is limited, and so too is the facilitation of skill development within an ecologically valid context. Objective: While numerous methods may be employed to address this, one resource which remains relatively unexplored is the StrideDeck Treadmill, therefore the purpose of this study was to investigate the effectiveness of this equipment with specific reference to the biomechanical changes for skating ability. Methods: N = 16 male athletes (Mage = 15.0 ± 0.76 yrs) from a junior league competition participated in this intervention based study. n = 9 were assigned to the training intervention (StrideDeck) once a week, while the control group (n = 7) continued their normal training routines. Further, monthly sprint tests both on the StrideDeck and an on-ice protocol were conducted to track progress via kinematic analysis. Results: Data analysis revealed no significant overall effects for on-ice sprint skating performance after StrideDeck training; however there were significant kinematic differences between StrideDeck and ice conditions. Conclusions: Therefore while the StrideDeck may have merit in regard to physiological paramters, the results of this study do not support its use as a skill acquisition tool in regard to increasing skating ability.